Review on asset management of power transformer by diagnosing incipient faults and faults identification using various testing methodologies. (October 2021) - Soni, Rahul; Mehta, Bhinal
Highlights: Root cause analysis is pivotal to diagnose incipient faults of power transformer. Asset life can be improved to avoid premature failure by condition monitoring. Chemical, electrical and special tests are integral for reliable performance. Online as well as offline detection techniques predict internal faults proactively. Remedial suggestions of replace, refurbish and maintenance for asset is decisive. Abstract: Power transformers are most imperative and critical element in electrical power system grid. To have a consistent electricity supply it is obligatory to give substantial attention for upkeep of the transformer. To capitalize on the lifespan and reliability of transformers, it is significant to be aware of the ageing and damage of any internal as well as external parts such as winding, core, tap changer, bushings etc. of power transformers. Condition monitoring is a significant protagonist in asset performance management approach and right diagnosis will provide the indication of probable faults that may occur and means to get rid of it. For accurate measurements of failure chances and to estimate residual life of power transformers, industry standards have defined certain methods in order to associate outcomes from several routines, type and special tests. This paper covers a comprehensive review on established tests as a part of chemical, electrical and miscellaneous incipient faults such as dissolved gas analysis, oil testing methods, sweep frequency response analysis, recovery voltage method, partial discharge, infrared thermograph test, turns ratio test, dielectric dissipation factor, transformer winding resistance, core to ground test, and insulation resistance calculation. It also contemplates the practices extensively helpful for measuring the health index, lifecycle enhancement, condition-based assessment and probability of failures. This paper summarizes a comprehensive assortment of methods extracted from industry and academic resources and distinguishes internal faults in an integrated structure with inclusion of health index formulation and interpretation for lifecycle prediction and possible suggestions to improve the asset condition. Index Terms - Power Transformer, Incipient Faults, Condition Based Assessment, Health Index, Failure Analysis.